2011
DOI: 10.1074/jbc.m111.233874
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Intracellular Manganese Homeostasis by Kufor-Rakeb Syndrome-associated ATP13A2 Protein

Abstract: Mutations in the ATP13A2 gene are associated with KuforRakeb syndrome (KRS) and are found also in patients with various other types of parkinsonism. ATP13A2 encodes a predicted lysosomal P5-type ATPase that plays important roles in regulating cation homeostasis. Disturbance of cation homeostasis in brains is indicated in Parkinson disease pathogenesis. In this study, we explored the biological function of ATP13A2 as well as the pathogenic mechanism of KRS pathogenic ATP13A2 mutants. The results revealed that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
139
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(145 citation statements)
references
References 54 publications
6
139
0
Order By: Relevance
“…Although we recapitulate the cell-protective effects of ATP13A2 in conditions of Mn 2+ and Zn 2+ toxicity, our biochemical analysis indicates that in contrast to what was suggested in the literature (7)(8)(9)(10)(11)(12), ATP13A2 most likely is not a Mn 2+ or Zn 2+ transporter, as the steady-state levels of autophosphorylated ATP13A2 remain unaffected by Mn 2+ or Zn 2+ .…”
Section: Discussionmentioning
confidence: 40%
See 2 more Smart Citations
“…Although we recapitulate the cell-protective effects of ATP13A2 in conditions of Mn 2+ and Zn 2+ toxicity, our biochemical analysis indicates that in contrast to what was suggested in the literature (7)(8)(9)(10)(11)(12), ATP13A2 most likely is not a Mn 2+ or Zn 2+ transporter, as the steady-state levels of autophosphorylated ATP13A2 remain unaffected by Mn 2+ or Zn 2+ .…”
Section: Discussionmentioning
confidence: 40%
“…The catalytic turnover of P-type ATPases depends on the presence of the substrate to be transported (13). Because ATP13A2 may be a Mn 2+ (7)(8)(9) or Zn 2+ (10-12) pump, we tested whether Mn 2+ or Zn 2+ activate ATP13A2 turnover. However, the steady-state phosphorylation levels were unaffected by 100 μM MnCl 2 or ZnCl 2 , indicating that ATP13A2 is unlikely to transport Mn 2+ or Zn 2+ (Fig.…”
Section: Atp13a2 Undergoes Autophosphorylation and Accumulates In Thementioning
confidence: 99%
See 1 more Smart Citation
“…This dependence of the GFP-Spf1 ATPase with Mg 2ϩ is similar to that of other P-ATPases where Mg 2ϩ acts as cofactor. A recent study has shown that the human P5B-ATPase ATP13A2 plays a role in regulating the intracellular manganese concentration (22). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Of the proteins postulated to be involved in manganese detoxification/efflux, the Golgi-localized secretory pathway Ca 2ϩ -ATPase 1 (SPCA1), which is an ortholog of S. cerevisiae Pmr1p, is comparatively well charac-terized (15)(16)(17). Moreover, ATP13A2/PARK9 (hereafter ATP13A2) is involved in manganese detoxification (18) based on the observation that the S. cerevisiae ortholog Ypk9p protects cells from toxicity of manganese and other metals by vacuolar sequestration (19,20). Importantly, loss-of-function mutations of the ATP13A2 gene were identified to cause an autosomal recessive form of early-onset parkinsonism (KuforRakeb syndrome) (21).…”
mentioning
confidence: 99%